Strength training for men the ultimate core strength to power conversion training system - Collins, Paul, 1970- (Body coach series, 2010)
Helps to add a fresh dimension to muscular development with its 'Core-Power' Conversion Training System that takes the guesswork out of training and offers a different learning experience for achieving the ultimate athletic body